Correlations between physiological and kinematic variables in assessment of swimmers`exertion - Makar, P.; Bielec, G. (Journal of Sports Science & Medicine, 2012)
The factors assessing athletes` commitment in performed physiological tests are not commonly discussed in literature. Proper interpretation of test results depends on conscientious workout performed by athlete. Permanent analysis of physiological variables together with measurement of kinematics parameters is essential in planning long-term athlete development. The aim of the study was to present correlations between physiological and kinematic variables as the factors determining swimmers` involvement in performance of 5x200m step test. We wanted to discover individual relationships between lactate concentration (LA) and stroke length (SL), stroke rate (SR), stroke index (SI), turns velocity and swimming velocity. Methods: Four junior swimmers (3 male and 1 female) aged 16±0.4 years, participated voluntarily in the study. They all presented high level of sport competence, placing in finals of national junior championships. The study was conducted using a 5x200 m backstroke step test which consists of five 200-metre bouts that must be covered with increasing pace every subsequent repeat. The first bout was completed with 75-80% of the maximal velocity for the distance, the second with 81-85%, the third with 86-90%, the fourth with 91-95%, and the last one with maximal velocity. Breaks between the repeats lasted 3, 5, 7 and 20 minutes respectively. Capillary blood samples were drawn from the ear lobe 1 minute after each repeat. Time measurement was done with the use of 25 Hz Sony camera and a professional computer software (Adobe Premiere Pro v7.0). The software calculated turns and swimming velocity as well as stroke length, stroke rate and stroke index. Pearson`s coefficient was used in assessment of correlations between kinematic variables and lactate values. The level of statistical significance was set at P < 0.05. Results: Mean values of Pearson`s coefficient showed significant correlations between lactate and most analysed kinematics variables. Mean LA concentration during maximal effort was 12.12 mmol/l The highest relations were observed between lactate and stroke rate (r = 0.98, p < 0.05). The lowest and non-significant liaisons were found between lactate and stroke index (r = 0.62, p > 0.05). Lactate concentration was correlated insignificantly with stroke length and turns velocity in one participant. Conclusions: The analysis of lactate concentration and kinematics variables revealed individual diversity. It is suggested that correlation value may be an indicator determining swimmers` involvement in exertion tests.